Water level control of a small hydropower plant with a surge tank. Issue 2 (4th March 2017) - Borkowski, Dariusz
ABSTRACT: This paper presents an application of a small hydropower plant (SHP) embedded in a hydraulic system with a surge tank of a relatively low water volume. To maintain a stable surge tank water level the author used a precisely designed PI-type controller. The analytical design method, the so-called root locus, was used in this work. A new identification method that uses the step response to identify the parameters of a real system is described. The proposed method, analytical models of hydraulic system and turbine as well as water level controller were implemented and tested in a real 55 kW grid connected SHP utilizing treated water from a wastewater treatment plant. The results of the tests conducted under substantial variations of the water flow confirmed the stable operation of the controller at the maximum water level fluctuations of ±5 cm during a normal operation.